Determinan Tingkat Literasi Keuangan Siswa Sekolah Menengah (Studi Komparatif Indonesia dan Vietnam) - Fatih Atsaris Sujud; Khasan Setiaji (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2020)
Financial literacy is an individual ability to make decision on it’s financial regulation. An individu has to have knowledge and skill to set his financial resources effectively to gain his prosperity. Financial literacy is influenced by many factors, such as gender, education andincome of parent those become the purpose of this research. The population of this study was students of SMA Hidayatullah and THPT Tran Nhan Tong. Saturated sampling was used as the method of sampling from 246 respondents. In analyzing the data, the writer used Mann Whitney method. The result showed that there was difference between gender and education of parent on influencing financial literacy under 0.05 asymptomatic significance, there was no difference income of parent on influencing towards financial literacy. Meanwhile there was difference of both countries’ financial literacy. For the suggestion, the students are expected to be more diligent to learn and apply their finanncial knowledge, meanwhile for the future researcher, is expected to find other variables those have big impact toward an individual’s financial literacy to get many more varied researches